2013
DOI: 10.1371/journal.pone.0062650
|View full text |Cite
|
Sign up to set email alerts
|

Towards Renewed Health Economic Simulation of Type 2 Diabetes: Risk Equations for First and Second Cardiovascular Events from Swedish Register Data

Abstract: ObjectivePredicting the risk of future events is an essential part of health economic simulation models. In pursuit of this goal, the current study aims to predict the risk of developing first and second acute myocardial infarction, heart failure, non-acute ischaemic heart disease, and stroke after diagnosis in patients with type 2 diabetes, using data from the Swedish National Diabetes Register.Material and MethodsRegister data on 29,034 patients with type 2 diabetes were analysed over five years of follow up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 36 publications
(37 reference statements)
1
38
0
Order By: Relevance
“…As expected, cardiovascular risks vary across study populations: the incidence of myocardial infraction and stroke per 1,000 person‐years were, respectively, 11.3 and 5.6 in the UK, and 13.5 and 12.1 in Sweden. By contrast, those of coronary heart disease and stroke were 7.6 and 7.1, respectively, in the Japanese study.…”
Section: Summary Of Health Economic Models For Diabetessupporting
confidence: 57%
See 2 more Smart Citations
“…As expected, cardiovascular risks vary across study populations: the incidence of myocardial infraction and stroke per 1,000 person‐years were, respectively, 11.3 and 5.6 in the UK, and 13.5 and 12.1 in Sweden. By contrast, those of coronary heart disease and stroke were 7.6 and 7.1, respectively, in the Japanese study.…”
Section: Summary Of Health Economic Models For Diabetessupporting
confidence: 57%
“…The incidence of a diabetic complication is viewed as a transition from a ‘no‐complication’ state to the disease state. The probabilities of each transition depend on the risk factors shown in Table , and the relationships between the probabilities and the risk factors are expressed as risk equations. Simulation by the UKPDS outcomes model 2 is carried out as the following steps on an annual cycle.…”
Section: Summary Of Health Economic Models For Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, none of the published, diabetes diseasestate simulation models, [20][21][22][23][24][25][26][27][28][29][30][31][32][33] including the recently published UKPDS Outcomes Model 2, 34 takes into account currently available medical and surgical treatments. For the general population, various CHD policy models exist.…”
mentioning
confidence: 99%
“…Another result from the validation of the IHE Cohort Model for Type 2 Diabetes was the importance of choosing sets of risk equations that match the decision context as regards time and place. In this cost-effectiveness analysis, we applied recently published Swedish macrovascular risk equations 32 . The one-way sensitivity analyses performed indicated that results and their interpretation were robust to changes in frequency of hypoglycemia associated with third-line insulin treatment, increasing initial BMI or a more invasive treatment programme where the second-line treatment is initiated at HbA1c 7% instead of starting at baseline values from trials (8.3% and 8.4%).…”
Section: Discussionmentioning
confidence: 99%